2020
DOI: 10.2217/hep-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

JAK/STAT signaling in hepatocellular carcinoma

Abstract: Liver cancer is the second most lethal cancer in the world with limited treatment options. Hepatocellular carcinoma (HCC), which accounts for more than 80% of all liver cancers, has had increasing global incidence over the past few years. There is an urgent need for novel and better therapeutic intervention for HCC patients. The JAK/STAT signaling pathway plays a multitude of important biological functions in both normal and malignant cells. In a subset of HCC, JAK/STAT signaling is aberrantly activated, leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 102 publications
1
48
0
Order By: Relevance
“…The signal transducer and activator of transcription (STAT) protein family has seven members, STAT1-5, STAT5B, and STAT6 [ 135 , 136 ]. STAT3 has been found to be involved in promoting HCC development and malignant and cancer stemness characteristics [ 134 , 135 , 137 , 138 , 139 ]. When IGF/IGF-1R signaling was deactivated by miR-486-5p or siRNA-IGF-1R, the levels of STAT3, mTOR, and cMyc were reduced, and colony formation was suppressed [ 140 ].…”
Section: Igf/igf-1 Signaling In Hccmentioning
confidence: 99%
“…The signal transducer and activator of transcription (STAT) protein family has seven members, STAT1-5, STAT5B, and STAT6 [ 135 , 136 ]. STAT3 has been found to be involved in promoting HCC development and malignant and cancer stemness characteristics [ 134 , 135 , 137 , 138 , 139 ]. When IGF/IGF-1R signaling was deactivated by miR-486-5p or siRNA-IGF-1R, the levels of STAT3, mTOR, and cMyc were reduced, and colony formation was suppressed [ 140 ].…”
Section: Igf/igf-1 Signaling In Hccmentioning
confidence: 99%
“…It is thus conceivable that persistent HCV-induced signaling alterations and deranged cytokine production may promote the development of extrahepatic manifestations in immune cells [148]. Several compounds targeting these signaling pathways have been suggested for chemoprevention of HCC (reviewed in detail in [149,150]) and targeting HCV-relevant pathways to treat established HCC have been suggested [151][152][153]. Therefore, learning from HCV-induced liver disease will help to develop novel diagnostics and personalized therapeutic concepts that may be useful to prevent and potentially also to treat HCC from other related liver disease etiologies like NAFLD.…”
Section: Clinical Implications For Biomarker Discovery To Predict Hcvmentioning
confidence: 99%
“…The JAK/STAT signaling pathway plays crucial roles in many cell progresses, including cell proliferation and immune response. Many studies have reported that JAK/STAT signaling is aberrantly activated in HCC and activated JAK/STAT pathway causes dysregulation of its many downstream target genes correlated with proliferation, immune, invasion, and metastasis [ 18 , 19 ]. In addition, hepcidin activates the JAK/STAT pathway through Jak2 activation and transcription factor Stat3 phosphorylation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%